THE EFFECT OF SHOPPING MALL’S ATTRIBUTES TOWARD CUSTOMER SATISFACTION OF ABC Mall AND XYZ Mall - Cynthia Astono (iBuss Management, 2014)
With the tight competition among shopping malls in Surabaya, it lead towards the concept war between them to stay longer within the industry. Currently, there are two shopping malls, which are in the middle of tight competition; they are ABC Mall and XYZ Mall. Although ABC Mall is the newest entrant of shopping mall in Surabaya, XYZ Mall as the old player is still developing. Thus, this research aims to analyze and find out which shopping malls’ attribute that able to increase the customer satisfaction. There are five shopping mall’s attributes, they are convenience, mall’s environment, tenant presence, service quality, and marketing focus. From those five attributes, 156 questionnaire data collected by using simple random sampling and analysed using multiple linear regression method, results findings shows that four out of five attributes show significant effect toward customer satisfaction. They are convenience, mall’s environment, service quality, and marketing focus. Keywords: Mall, Attributes, Shopping, Customer Satisfaction.